Магістратське правління в сотенних містечках Чернігово-Сіверщини (на прикладі міст Стародубського полку) - Доманова, Г.С. (Сіверщина в історії України, 2021)
У статті розглядаються питання щодо запровадження магістратського правління в сотенних центрах Чернігово-Сіверщини
на прикладі міст Стародубщини (Мглин, Погар та Почеп), з’ясована їхня подальша доля і непрості взаємини із козацьким урядом. Поява маґдебургій у містах забезпечувалася королівськими привілеями,
царськими грамотами, гетьманськими універсалами, які давали дозвіл на міське самоврядування. Відтак, проаналізовано королівський
привілей на маґдебурзьке право 1626 р., який одержав Мглин, царські грамоти 1665–1666 рр., які гарантували існування маґдебургій
у Почепі, Погарі й Мглині. З’ясовано, що міщанські громади були зацікавлені у збереженні своїх прав, утім спроби врегулювати стосунки з козацькою спільнотою виявилися недостатньо ефективними. У
другій половині ХVІІІ ст. Почеп і Мглин втратили статус повітових міст, а заразом і право на міське самоврядування, перейшовши
у володіння гетьмана К. Розумовського. A few towns in Chernihiv-Sivershchyna’s had self-governing status during
the second half of the XVII–XVIII c. First of all, the self-governing status was
secured by royal charters on Magdeburg law. Regimental towns – Chernihiv,
Nizhyn, Starodub – received their first privileges from the Polish King Sigismund
III. They retained the magistrate’s rule until the entry into force of the “Gorodovogo
polozheniya” of April 21, 1785, when they were already part of the Russian
Empire. The burghers’ communities of some sotennykh towns also joined
the self-governing traditions.
The article considers the introduction of the magistrate’s rule in the sotennykh
of centers of Chernihiv-Sivershchyna’s on the example of the towns of Starodub
(Mhlyn, Pohar and Pochep), their future fate, as well as the coexistence of classes
by nature of the burghers and cossack`s administrations. The emergence of Magdeburg
law in the towns was ensured by royal privileges, royal charters, hetman’s
universals, which gave permission for the introduction of town self-government.
The royal privilege on the Magdeburg law of 1626 was analyzed. This privilege
was given to the town of Mhlyn during the Polish rule in the region. The royal
charters of 1665–1666, which guaranteed the existence of the magistrate government
in Pochep, Pohar and Mhlyn during the second half of the XVII–XVIII
c., were analyzed. It was found that the burghers’ communities were interested
in preserving their rights, but attempts to settle relations with the cossack community
were not eff ective enough. The first half of the ХVІІІ century marked by
the active struggle of burghers’ communities. Dual power in the sotennykh centers,
as well as regimental cities, led to the decline of magistrate rule. In the second
half of the eighteenth century Pochep and Mhlyn finally lost the status of
a county town, as well as the right to municipal self-government. They passed
into the possession of Hetman K. Rozumovskyi. The Pohar magistrate retained
the magistrate government despite the encroachment of the sotennykh officers,
although he had some restrictions on his activities.